ENT300 Heaven sky ice cream enterprise / Sharifah Khairunnisa Tuanku Hadward... [et.al] - Tuanku Hadward, Sharifah Khairunnisa; Madang, Roslind Para; Engkamat, Rose Nawai; Bajug, Embrissavlyncca (2015)
Live your Life is the name of company name of the Heaven Sky Ice Cream Enterprise. This business is created by four members that are also acting as a manager to this business. By this we were agree to contribute some of amount to starting the business. The main activities make and supply our product to secondary school, primary school and our company itself. The customer satisfaction is the number one priority to us. Our business operation Hour is between 9.30 am to 10.30 pm every Monday to Thursday, Saturday and Sunday. Other than that, we are closed in Friday.